The Economy of Political of Media on the News on the 2017 Banten Governor Election: Case of Radar Banten and Baraya TV - Priatna, Achmad Nashrudin (LPPM Universitas Bina Bangsa, 2021)
Mass media, both print and broadcast (TV and radio), play an essential role in disseminating critical messages to the public/community. Because the media in the current era has become an economic and political commodity because of its function and ownership, which is owned by individuals (owners of capital). This positions the media and processes as disseminators of information and motivates for-profit and political interests. This article discusses the position of the local Press in Banten, namely Radar Banten and Baraya TV. In the euphoria of the gubernatorial election, these two media inevitably convey political messages. At the same time, these two media will try to make a profit just like an economic institution. How is the positioning of these two media, which have the function of disseminating information and education but simultaneously practicing economic and political activities? Are these two media able to maintain independence